International Coordination of Fiscal Policy in Limiting Economies - Chari, V. V.; Kehoe, Patrick J. (Journal of Political Economy, 1990)
We examine the limiting behavior of cooperative and noncooperative fiscal policies as countries' market power goes to zero. We show that these policies converge if countries raise revenues through lump-sum taxation. However, if there are unremovable domestic distortions, such as distorting taxes, there can be gains to coordination even when a single country's policy cannot affect world prices. These results differ from the received wisdom in the optimal tariff literature. The key distinction is that, contrary to the tariff literature, the spending decisions of governments are explicitly modeled.